Influence of the applied load on the creep behaviour of tin-silver-copper solder - Soares, Delfim (2020)
During the life cycle of an electronic printed circuit boards (PCBs), the cold solder joints formation between the component and PCB are a failure mode that happen commonly. This phenomenon is related to solder joint fatigue and is attributed mainly to the mismatch of the coefficients of thermal expansion (CTE) of component-solder-PCB assembly. With today's solder joint thickness decreasing and increasing working temperatures, among others, the stresses and strains due to temperature changes are growing, leading to limited fatigue life of the products. In this way, once as fatigue life decreases with increasing plastic strain, it is important to study creep occurrence, especially during thermal cycles.In this work, a dynamic mechanical analyser (DMA) was used to study the influence of different applied load and temperature on the creep behaviour of the solder during a sequence of cycles. For these tests, different SAC405 alloy samples were produced, all in the same processing conditions. Creep tests were made on three-point-bending clamp configuration, isothermally at 303, 323 and 348 K, under three separate applied load of 3, 5 and 9 MPa.The results show that creep rate has an important decrease from the 1st to the following applied creep cycles. This behaviour occurs for all the tested loads and temperatures. Results, also, show that the main creep mechanisms changes, from a diffusion base type, for low load and different temperatures, to a dislocation glide-climb type for an applied load of 9 MPa and temperatures from 303 to 348 K. Experimental determined n exponent for the tested conditions allows the correlation between creep mechanisms and experimental parameters (applied load and temperature).